Effect of Magnetic Field on Rheological Properties of Cellulose Ether Solutions - Vshivkov, Sergey A.; Rusinova, Elena V.; Galyas, Andrei G. (Journal of Composites and Biodegradable Polymers, 2014)
Application of a magnetic field is shown to be accompanied by an increase in the viscosity of hydroxyethyl cellulose, ethyl cellulose solutions and sodiumcarboxymethyl cellulose solutions in 2 - 4 times. The concentration dependences of solution viscosity in the presence of a magnetic field are described by curves with maxima.